Synthesis of six-coordinate mono-, bis-, and tris(tetrazolato) complexes via [3 + 2] cycloadditions of nitriles to silicon-bound azido ligands. Issue 43 (13th October 2016) - Portius, Peter; Davis, Martin
Abstract : The unusual situation presented by a silicon centre coordinating four 1, 3-dipolar ligands is exploited in thermally activated cycloaddition reactions with nitriles that lead to six-coordinate poly(tetrazolato) complexes of silicon. Abstract : A convenient synthetic route to poly(tetrazolato) silicon complexes is described based on the four reactive centres of the N-rich, highly endothermic tetraazides of the type Si(N3 )4 (L2 ). Hypercoordinate azido(tetrazolato) silicon complexes Si(N3 )2 (N4 C-R)2 (L2 ), R = CH3, C6 H5, 4-C6 H4 CH3 (4a, 5, 6, 7 ) and Si(N3 )2 (N4 C-L)2 (9, L = 2-C5 H4 N), L2 = 2, 2′-bipyridine, 1, 10-phenanthroline, with SiN6 skeletons were synthesised via multiple [3 + 2] dipolar cycloaddition reactions starting from Si(N3 )4 (L2 ) and a nitrile. The isolated new complexes were characterised by standard analytical methods, single crystal X-ray diffraction and differential scanning calorimetry (4a, b ). Tetrazolato ligand linkage isomerism was observed for complex4a . The crystallographically characterised methyl tetrazolato complexes and plausible configurational and linkage isomers were evaluated by DFT calculations at the B3LYP/6-311G(d, p) level.